2003
DOI: 10.1016/s0378-1097(02)01198-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress in the regulation of H2S production during ultradian metabolic oscillation ofSaccharomyces cerevisiae

Abstract: Periodic evolution of H 2 S during aerobic chemostat culture of Saccharomyces cerevisiae resulted in ultradian metabolic oscillation via periodic inhibition of respiratory activity. To understand the nature of periodic H 2 S evolution, we investigated whether oxidative stress is associated with H 2 S production. The cellular oxidative states represented by intracellular level of lipid peroxides oscillated out of phase with the oscillation of dissolved O 2 . Pulse addition of antioxidant, oxidative agent or inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…It was suggested that oxidative stress acts as a trigger for H 2 S production, which itself acts as a redox regulator when the level of oxidative stress exceeds the antioxidant capacity of the cell. (87)(88)(89) This tight relationship suggests that the origin of mitochondrial endosymbionts may be based on a syntrophic association between a sulphide-oxidizing aproteobacterium and an archaeal sulphide-producing host.…”
Section: The Driving Force For Endosymbiosismentioning
confidence: 98%
“…It was suggested that oxidative stress acts as a trigger for H 2 S production, which itself acts as a redox regulator when the level of oxidative stress exceeds the antioxidant capacity of the cell. (87)(88)(89) This tight relationship suggests that the origin of mitochondrial endosymbionts may be based on a syntrophic association between a sulphide-oxidizing aproteobacterium and an archaeal sulphide-producing host.…”
Section: The Driving Force For Endosymbiosismentioning
confidence: 98%
“…The activities of H2S synthesizing enzymes also have a significant positive correlation with the plasma H 2 S levels. Previous studies in this direction suggest that oxidative stress results in periodic depletion of glutathione and cysteine, which in turn causes stimulation of the assimilation pathway and H 2 S production 35 in Saccharomyces cerevisiae model. Wei-Ning Niu et al demonstrated the potential for increased H 2 S production under oxidative stress conditions in tissues where cystathione beta synthase activity is increased by s-glutathionylation.…”
mentioning
confidence: 92%
“…In plants, the respective enzymes for oxidative burst caused by pathogen attack or mechanical wounding are primarily ascribed to the plasma membrane-located NADPH oxidases, homologs of the mammalian gp 91phox respiratory burst NADPH oxidase subunit (Orozco-Cardenas et al, 2001;Torres et al, 2002;Sagi et al, 2004). ROS generated by plasma membrane-located NADPH oxidases also play an important role in regulating plant growth and development, including the growth of root hair and pollen tube (Foreman et al, 2003;Potocky et al, 2007), stomata closure (Kwak et al, 2003;Cho et al, 2009;Srivastava et al, 2009), lignification in differentiating xylem vessels (Barceló, 2005), seed after-ripening (Muller et al, 2009), and seed dormancy (Liu et al, 2010). In addition, exogenous H 2 O 2 has a positive effect on the cotton fiber initiation , and the H 2 O 2 generated from extracellular peroxidases and CuZn-superoxide dismutase (SOD) is required for seed germination in Pisum sativum (Kranner et al, 2010) and for the development and lignification of the secondary walls of tracheary elements in the Zinnia cell-culture system (Karlsson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%